Modelo Prolab: Al Reskate, una propuesta sostenible para reducir la cantidad de desperdicio de productos de consumo próximos a vencer o de baja rotación - Jordán Zelada, Erika Nelly (2024)
This thesis focuses on addressing the problem of food waste in the mass consumption sector in Peru, as food waste is a critical issue affecting both the environment and the economy. In Peru, 12.8 million tons of food are discarded yearly, causing significant environmental pollution and economic loss. The lack of planning and inadequate disposal of these products exacerbate the problem. It is worth noting that the mass consumption market in Peru is recovering, with the growing adoption of e-commerce a trend towards seeking cost- effective options, and an increasing interest in environmental care. The results of the study conducted in Metropolitan Lima indicate a willingness on the part of both suppliers and buyers to purchase near-expiration or low-rotation products, alongside an interest in environmental care. Although several platforms offer delivery and online shopping services, none focus on rescuing products. In response, an innovative solution is proposed through a digital platform called "Al Reskate," which aims to connect sellers with products nearing their expiration date or with low turnover to consumers interested in purchasing these products at reduced prices. This platform offers features such as product visualization, nearby points, pickup methods, and payment options. The business model emphasizes sustainability and the circular economy, aligning with SDGs 12.4 and 12.6, which seek environmentally sound waste management and promote sustainable practices. The financial analysis shows a positive net profit with a Net Present Value (NPV) and Internal Rate of Return (IRR) of S/ 4,546,731 Soles and 110%, respectively. In addition to that, a Social NPV of S/937,210 Soles is projected.